If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying (n + 18) + 2n = 90 Reorder the terms: (18 + n) + 2n = 90 Remove parenthesis around (18 + n) 18 + n + 2n = 90 Combine like terms: n + 2n = 3n 18 + 3n = 90 Solving 18 + 3n = 90 Solving for variable 'n'. Move all terms containing n to the left, all other terms to the right. Add '-18' to each side of the equation. 18 + -18 + 3n = 90 + -18 Combine like terms: 18 + -18 = 0 0 + 3n = 90 + -18 3n = 90 + -18 Combine like terms: 90 + -18 = 72 3n = 72 Divide each side by '3'. n = 24 Simplifying n = 24
| -23=2x+3x+2 | | x/3-3=-2 | | 6(x/6)-6(4)=6(x/6) | | -17x+18=13 | | x-7=1-9 | | -7=5-2n+6n | | a+(a-15)=55 | | -8-n=0 | | 8p+3=3p+13 | | 5n+3=14-5n | | -2x+5-5x=5 | | 68mi/h=mi/sec | | (-14xy^2)/(21y^3)= | | 8x-(3x-11)=36 | | 4y=2x+9solve | | 3b^2+7b-6= | | 0.4x-8=9-0.6x | | -5=6x-4x+1 | | 72+6y=-6y | | 5x^2-2x-365=0 | | 40x+8y=48 | | 4p+7=3p+11 | | (5y-4z)(7y+3z)= | | -6=5x-7x-6 | | 4(-3+x)=5x-0.25 | | -b=11 | | 6x-9=3(x+4) | | -(2x-7y+4)= | | 3r+25=-1 | | 19x=-20 | | (7+v)(2v-9)=0 | | -4z+7=-6z-29 |